Mechanical and electro-mechanical properties of three-dimensional nanoporous graphene-poly(vinylidene fluoride) composites - G. P. Zheng; Z. Y. Jiang; Z. Han; J. H. Yang (eXPRESS Polymer Letters, 2016)
Three-dimensional nanoporous graphene monoliths are utilized to prepare graphene-poly(vinylidene fluoride) nanocomposites with enhanced mechanical and electro-mechanical properties. Pre-treatment of the polymer (poly(vinylidene fluoride), PVDF) with graphene oxides (GOs) facilitates the formation of uniform and thin PVDF films with a typical thickness below 100 nm well coated at the graphene nano-sheets. Besides their excellent compressibility, ductility and mechanical strength, the nanoporous graphene-PVDF nanocomposites are found to possess high sensitivity in strain-dependent electrical conductivity. The improved mechanical and electro-mechanical properties are ascribed to the enhanced crystalline β phase in PVDF which possesses piezoelectricity. The mechanical relaxation analyses on the interfaces between graphene and PVDF reveal that the improved mechanical and electro-mechanical properties could result from the interaction between the –C=O groups in the nanoporous graphene and the –CF2 groups in PVDF, which also explains the important role of GOs in the preparation of the graphene-polymer nanocomposites with superior combined mechanical and electro-mechanical properties.